Kummerowia striata extract protects paracetamol-induced liver injury by modulating the S1P/Nrf2/Keap1 pathway - Huanghui Qin; Runxiao Chen; Youlan Xie; Hang Liu; Yubo Xiao; Lanyu Li (PLoS ONE, 2025)
Background Drug-induced liver injury remains a significant challenge in both drug development and clinical applications. Acetaminophen (APAP), a commonly used analgesic and antipyretic, can cause liver damage when overdosed, with APAP-induced liver injury being one of the leading causes of acute liver injury. Kummerowia striata (Ks), a leguminous plant, has been reported to contain chemical compounds with anti-inflammatory and antioxidant activities. However, its potential therapeutic effects in liver diseases remain inadequately explored. Objective This study aims to investigate the protective effect of Kummerowia striata extract against APAP-induced acute liver injury and further explore its potential molecular mechanisms. Methods C57BL/6J mice were pre-treated with Ks extract by gavage for 3 days. On the second day, treatment was discontinued, and the mice were fasted for 16 hours. After the fasting period, the final dose of Ks extract was administered, followed by an intraperitoneal injection of APAP (300 mg/kg) 1 hour later to establish a drug-induced liver injury model. Tissue samples were collected 24 hours after modeling. To investigate the molecular mechanisms by which Ks extract prevents APAP-induced acute liver injury, network pharmacology, the GEO database, and molecular docking analysis were employed. Results Ks extract exhibited a significant gender-independent protective effect in preventing APAP-induced acute liver injury in mice. In male mice, Ks extract attenuated the occurrence of acute liver injury by modulating the sphingosine-1-phosphate/ Sphingosine-1-Phosphate Receptor 2/ Sphingosine-1-Phosphate Receptor 4(S1P/S1PR2/S1PR4) signaling pathway and the upstream regulator SPHK1. This, in turn, regulated the binding of Kelch Like ECH Associated Protein 1 (Keap1) to Nuclear factor erythroid 2-related factor 2(Nrf2), alleviating oxidative stress and inflammatory responses. Discussion This study illustrates that Ks exerts a protective effect against APAP-induced acute liver injury by modulating oxidative stress and inflammatory responses through multiple mechanisms. Notably, Ks inhibited Keap1 expression and restored Nrf2 signaling, indicating a potential regulatory role in mitigating mitochondrial oxidative damage and ferroptosis. Furthermore, Ks downregulated SPHK1 expression and reduced levels of the bioactive sphingolipid S1P, as well as its receptors S1PR2 and S1PR4, unveiling a previously unreported involvement of the SPHK1/S1P/S1PR2/4 axis in liver injury. Interestingly, sex-based differences in APAP hepatotoxicity were observed, with female mice exhibiting lower susceptibility, yet still responding to Ks treatment. These findings not only validate the hepatoprotective potential of Ks but also provide new mechanistic insights involving the Nrf2/Keap1 and S1P/S1PR2/S1PR4 signaling pathways, thereby laying a foundation for its development as a candidate therapeutic agent for acute liver injury.